The extent of the preserved feathers on the four-winged dinosaur Microraptor gui under ultraviolet light. - David W E Hone (Public Library of Science (PLoS), 2010)
Background The holotype of the theropod non-avian dinosaur Microraptor gui from the Early Cretaceous of China shows extensive preservation of feathers in a halo around the body and with flight feathers associated with both the fore and hindlimbs. It has been questioned as to whether or not the feathers did extend into the halo to reach the body, or had disassociated and moved before preservation. This taxon has important implications for the origin of flight in birds and the possibility of a four-winged gliding phase. Methodology/principal findings Examination of the specimen under ultraviolet light reveals that these feathers actually reach the body of the animal and were not disassociated from the bones. Instead they may have been chemically altered by the body tissues of the animal meaning that they did not carbonise close into the animal or more likely were covered by other decaying tissue, though evidence of their presence remains. Conclusions/significance These UV images show that the feathers preserved on the slab are genuinely associated with the skeleton and that their arrangement and orientation is likely correct. The methods used here to reveal hidden features of the specimen may be applicable to other specimens from the fossil beds of Liaoning that produced Microraptor.